2016
DOI: 10.1590/1414-431x20165229
|View full text |Cite
|
Sign up to set email alerts
|

Does the incremental shuttle walk test require maximal effort in young obese women?

Abstract: Obesity is a chronic disease with a multifaceted treatment approach that includes nutritional counseling, structured exercise training, and increased daily physical activity. Increased body mass elicits higher cardiovascular, ventilatory and metabolic demands to varying degrees during exercise. With functional capacity assessment, this variability can be evaluated so individualized guidance for exercise training and daily physical activity can be provided. The aim of the present study was to compare cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
2
9
0
2
Order By: Relevance
“…In the literature it is reported that beyond gender, other factors that influence VO 2 peak as genetic factors, age, weight, and training [31]. Findings similar to our study were found in obese women, where there was a significant correlation between the VO 2 peak in the cardiopulmonary exercise test with the ISWT VO 2 peak and the ISWT distance [5]. In this same study, the variables age and distance walked by the ISWT explained the predictive model for the VO 2 peak.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In the literature it is reported that beyond gender, other factors that influence VO 2 peak as genetic factors, age, weight, and training [31]. Findings similar to our study were found in obese women, where there was a significant correlation between the VO 2 peak in the cardiopulmonary exercise test with the ISWT VO 2 peak and the ISWT distance [5]. In this same study, the variables age and distance walked by the ISWT explained the predictive model for the VO 2 peak.…”
Section: Discussionsupporting
confidence: 87%
“…Our study presents differentials when proposing a prediction equation for VO 2 peak, the main variable for evaluation of cardiorespiratory fitness [19, 34], since most of the studies with ISWT focus on the prediction of walking distance [2, 10, 15, 17, 22, 23]. In addition, those who did the VO 2 peak prediction equation for women did not validate it [5, 11]. The equation developed in this study was validated in other volunteers and the VO 2 peak values obtained by the equation and the values of VO 2 peak obtained by the gas analyzer were similar, indicating that the application of the equation is feasible to estimate the VO 2 peak of the chosen population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Before starting the CPX, the volunteer remained in seated rest for two minutes, followed by two minutes of standing. A CPX with a maximum characteristic and/or symptom-limited was performed according to the Bruce protocol (12). This protocol presents progressive increases in speed and inclination every three minutes.…”
Section: Methodsmentioning
confidence: 99%